Tongue measurements and pharyngeal residue in amyotrophic lateral sclerosis - Augusto, Milena Magalhães; Da Silva, Roberta Gonçalves [UNESP]; Teixeira Dourado Júnior, Mario Emílio; Godoy, Juliana Fernandes; Lopes, Leonardo Wanderley; Pernambuco, Leandro (Taylor & Francis, 2021)
Aim: We aimed to analyze the relationship between tongue measurements and vallecular residue in patients with amyotrophic lateral sclerosis (ALS). Materials & methods: Twenty-one patients with ALS were assessed for posterior maximum tongue isometric pressure (PMTIP) and posterior tongue isometric endurance (PTIE) by the Iowa Oral Performance Instrument; vallecular residue after 10 ml of moderately thickened consistency by Fiberoptic Endoscopic Evaluation of Swallowing; and tongue thickness (TT) by ultrasonography. Results: PMTIP, PTIE and TT were decreased compared with the reference values for healthy individuals and were not different between patients with and without vallecular residue. Conclusion: In ALS, PMTIP, PTIE and TT are not good predictors of vallecular residue in the tested volume and food consistency.
Keywords: amyotrophic lateral sclerosis; deglutition; deglutition disorders; endoscopy; motor neuron disease; tongue